Green- and red-phosphorescent Mn(II) iodide complexes derived from 1, 3-bis(diphenylphosphinyl)propane. (15th September 2020) - Davydova, Maria P.; Yu Bagryanskaya, Irina; Bauer, Irina A.; Rakhmanova, Mariana I.; Morgalyuk, Vasilii P.; Brel, Valery K.; Artem'ev, Alexander V.
Graphical abstract: Two Mn(II) iodide complexes based on bis(diphenylphosphinyl)propane (dpppO2 ) has been synthesized and characterized by X-ray diffractometry, FT-IR and TGA techniques. Their luminescent properties have also been investigated. One of compounds, 1D coordination polymer, [Mn(dpppO2 )I2 ] n, display room temperature phosphorescence (λ max  = 530 nm) with unusually short lifetime being 50 µs. Highlights: Two Mn(II) iodide complexes derived from 1, 3-bis(diphenylphosphinyl)propane (dpppO2 ) were synthesized and characterized. [Mn(dpppO2 )I2 ] n emits green phosphorescence with the lifetime of 50 µs, and [Mn2 (dpppO2 )4 I2 ]l2 displays red phosphorescence with lifetime of 1400 µs. Abstract: The reaction of 1, 3-bis(diphenylphosphinyl)propane (dpppO2 ) with MnI2, depending on the reactants ratio, affords either 1D coordination polymer, [Mn(dpppO2 )I2 ] n (1 ), or cage-like complex [Mn2 (dpppO2 )4 I2 ]l2 (2 ). Polymer 1 contains Mn(II) ions in a tetrahedral [Mn@O2 I2 ] arrangement, while the metal ions of 2 feature a square-pyramidal [Mn@O4 I] geometry. At ambient temperature, 1 emits green phosphorescence (λ max  = 530 nm) with unusually short lifetime being 50 µs, while 2 displays long-lived red phosphorescence with λ max  = 660 nm and the lifetime of 1400 µs.